Extrauterine Adenomyoma of the Liver Mimicking a Hepatic Adenoma: A Case Report - Young Joo Won; Ji Young Woo; Jieun Byun; Min Eui Hong (대한영상의학회지, 2020)
Extrauterine adenomyoma of the liver is extremely rare. Only a few cases have been reported, and these reports have focused mainly on histopathology. Herein, we report the specific imaging findings of extrauterine adenomyoma of the liver in a 43-year-old woman with epigastric pain, which was initially diagnosed as a hepatic adenoma. CT and MRI revealed a solid and cystic mass with hemorrhagic foci and weak persistent enhancement, located in the subcapsular region of the right hepatic lobe.